Assessment of Biological Activity, Total Phenolic Content, and Cytotoxicity of Ethyl Acetate Extracts from an Endophytic Fungus, Lasiodiplodia pseudotheobromae IBRL OS-64 - Mat Jalil, Mohd Taufiq; Zakaria, Nurul Aili; Yahya, Mohd Fakharul Zaman Raja; Mohamad, Sharifah Aminah Syed; Ibrahim, Darah (Bogor Agricultural University, Indonesia, 2025)
The biological activities of ethyl acetate extracts of Lasiodiplodia pseudotheobromae IBRL OS-64 were assessed in the present study. Antioxidant activity was measured using the DPPH scavenging assay, antibacterial activity via broth microdilution, and total phenolic content using the Folin-Ciocalteu method. In vivo toxicity was determined using a brine shrimp lethality assay. The fraction extract exhibited the highest antioxidant activity, with an EC50 of 441.6 µg/ml, surpassing the crude extract's. The EEELP showed a relatively low phenolic content of 13.273 µg GAE/mg extract. Regarding antibacterial activity, both crude and fraction extracts demonstrated MIC values ranging from 62.5 to 250 µg/ml against Gram-positive bacteria, while MBC values ranged from 125 to 500 µg/ml for both extracts. The MIC values for crude and fraction extracts against Gram-negative bacteria were 250-500 µg/ml, whilst the MBC values for both crude and fraction extracts were in the range of 500–2,000 µg/ml. The findings also revealed that Gram-positive bacteria were more susceptible to both extracts (crude and fraction) than Gram-negative bacteria. The crude extract exhibited a non-cytotoxic effect with an LC50 value of 2054.88 µg/ml for acute exposure and a low cytotoxic effect with an LC50 value of 199.69 µg/ml for chronic exposure. Meanwhile, the fraction extract demonstrated a non-cytotoxic effect for both acute and chronic with an LC50 value of 5744.14 µg/ml and 1035.94 µg/ml, respectively. Therefore, the present study suggests that the fraction extract could be an effective pharmaceutical agent and safe for drug development due to its low toxicity.